To compare the outcome of local infiltration of corticosteroid and percutaneous release of pulley in treatment of trigger finger - Turkar, Rajesh; Jain, Siddharth (International Journal of Medical Research and Review, 2016)
Background: Stenosing tenosynovitis of fingers is one of the common tendinopathy attended in orthopaedic practice. A number of methods have been described for the treatment of this problem. Treatment ranges from conservative management to surgical procedures. Stenosing tenosynovit is also known as Trigger finger. Material & Methods: in this Prospective study all patients presented with trigger finger Grade 2 and 3 were randomly allocated into 2 groups. One group received local corticosteroid injection and in the other group, percutaneous release of pulley was performed as treatment option. These patients were then followed and assessed weekly over a period of two month and their progress noted. Results: We studied a total of 42 patients. Majority (71.4%) were females. The commonest age group is 40-50 years olds (56.6%).The most common presenting symptom was pain with triggering (52.3%). There was significant improvement in pain in the first two weeks in both groups but there was better improvement of pain in the corticosteroid group initially especially after first week. As for the triggering, there was significant improvement noted in first week in corticosteroid group but there was no difference in degree of improvement between both the groups after four week. The corticosteroid group had a complication rate of 10% whereas the percutaneous release group complication rate was 18.1%%. The recurrence rate was comparable in both the groups. Conclusion: Trigger finger is a common condition in orthopaedic practice. The commonly affected fingers are the centrally located on the palm. Local infiltration corticosteroid percutaneous release of pulley gives comparable results in long follow-up however corticosteroid injection gives better result initially with less complication.